2021
DOI: 10.3389/fgene.2021.689669
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of HSP90-RAR1-SGT1-Complex Members From Arachis Genomes and Their Responses to Biotic and Abiotic Stresses

Abstract: The molecular chaperone complex HSP90-RAR1-SGT1 (HRS) plays important roles in both biotic and abiotic stress responses in plants. A previous study showed that wild peanut Arachis diogoi SGT1 (AdSGT1) could enhance disease resistance in transgenic tobacco and peanut. However, no systematic analysis of the HRS complex in Arachis has been conducted to date. In this study, a comprehensive analysis of the HRS complex were performed in Arachis. Nineteen HSP90, two RAR1 and six SGT1 genes were identified from the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In addition, complete transcriptome analysis of heat-responsive genes in heat-sensitive genotypes (ICC 5912, ICC 4567, and ICC 10685) and heat-tolerant genotypes (ICC 15614, ICC 1356, and ICC 92944) has been also reported in chickpea [ 165 ]. Major gene families for heat stress like AP2/ERF gene family has also been reported in an earlier study [ 166 ]. One AP2 domain and three ERFs clustered with AP2 sequences have also been identified in chickpea [ 166 ].…”
Section: Genomics Interventionsmentioning
confidence: 53%
See 4 more Smart Citations
“…In addition, complete transcriptome analysis of heat-responsive genes in heat-sensitive genotypes (ICC 5912, ICC 4567, and ICC 10685) and heat-tolerant genotypes (ICC 15614, ICC 1356, and ICC 92944) has been also reported in chickpea [ 165 ]. Major gene families for heat stress like AP2/ERF gene family has also been reported in an earlier study [ 166 ]. One AP2 domain and three ERFs clustered with AP2 sequences have also been identified in chickpea [ 166 ].…”
Section: Genomics Interventionsmentioning
confidence: 53%
“…Major gene families for heat stress like AP2/ERF gene family has also been reported in an earlier study [ 166 ]. One AP2 domain and three ERFs clustered with AP2 sequences have also been identified in chickpea [ 166 ]. Deokar et al [ 167 ], also identified 16 AP2 and 120 putative ERF TFs in chickpea.…”
Section: Genomics Interventionsmentioning
confidence: 53%
See 3 more Smart Citations